The Usborne geography encyclopedia with complete world atlas (updated edition) - Doherty, Gillian; Claybourne, Anna Davidson, Susanna Abi-Ezzi, Nathalie Khanduri, Kamini (Usborne London, 2013)
Geography Encyclopedia